Cost-effectiveness analysis of different screening and diagnostic strategies for sexually transmitted infections and bacterial vaginosis in women attending primary health care facilities in Cape Town - Smith, Elise; Masson, Lindi; Passmore, Jo-Ann S.; Sinanovic, Edina (Frontiers in Public Health, 2023)
Background: Genital inflammation associated with sexually transmitted infections (STIs) and bacterial vaginosis (BV) is a key driver in the HIV epidemic. A new rapid point-of-care test (POC) that detects genital inflammation in women – Genital InFlammation Test (GIFT) – was recently developed by researchers at the University of Cape Town. The objective of this study was to establish the cost-effectiveness of this novel intervention relative to other relevant screening and diagnostic strategies for the management of STIs and BV in women seeking care in the public health sector in South Africa. Methods: A decision analysis model was developed for five different screening and diagnostic strategies for women incorporating syndromic management, screening with GIFT and using etiological diagnosis. A decision tree was constructed using Microsoft Excel Office 365, and cost and effectiveness parameters were obtained from published and unpublished literature. The model incorporated all clinic-level and treatment costs associated with diagnosing and treating a single episode of disease. The effectiveness of each approach was proxied by its sensitivity. One-way and threshold sensitivity analyses were conducted to test key uncertainties and assumptions in the model. Results: Screening with GIFT, and following with antibiotic treatment according to syndromic management guidelines for GIFT-positive cases, was the most cost-effective strategy with an incremental cost-effectiveness ratio (ICER) of USD 11.08 per women diagnosed with an STI(s) and/or BV and provided treatment. This strategy resulted in lower rates of overtreatment compared to syndromic management, but higher rates compared to etiological diagnosis using nucleic acid amplification tests and microscopy. However, following a GIFT positive test with etiological diagnosis prior to treatment did not increase the effectiveness, but dramatically increased the cost. Conclusion: Screening with GIFT and treating positive cases according to syndromic management guidelines is the most cost-effective strategy for the management of STIs and BV. GIFT has a potential to significantly improve the management of STIs and BV in women by identifying asymptomatic women and reducing their risk of HIV infection. This analysis presents a first step in establishing the cost-effectiveness of these interventions and paves the way for further research to develop optimal context-specific implementation strategies.